THE USED OF E-PROCUREMENT SYSTEMS IN GOVERNMENT AGENCIES: ISSUES AND CHALLENGES - Suzei Bt Mat Nuruddin; Zarina Bt Mohd Zain; Nur Alia Bt Mohd Nasir; Izzrin Nur Farhana Bt Rosman; Nor Suhaiza Bt Md. Khalid (International Journal of Accounting, Finance and Business, 2020)
Procurement can be defined in various ways and the procurement function is involvingthe activities and process of gaining the products, services and works. The main goal ofprocurement is to get the right categories of procurement at the right time, specific location andalso carrying out the process effectively and efficiently. In recent decades, there is so many issuesin government and this issue of procurement are increasing from time to time as it is become atrend of corrupt practices and abuse of power involving government agencies. Public Eprocurementis one of the important factors in public procurement reform and can play significantsupporting role in making governments more transparent and accountable. E- procurement is seenas an effective way to better support transparency and accountability. In conjunction, even thoughMalaysia already implement e-procurement system but still there is high rate of procurement issue.So there must be lacking toward the system itself. Hence, the main purpose of this study is to studythe ineffectiveness of e-procurement system in Malaysia. This research focus on the reasons forineffectiveness of the systems and try to identify the impact from the poor system used inprocurement. Finally, this research also aims to evaluate action taken by government in order tosolve the ineffectiveness of e-procurement system. Ten informants been selected using purposivesampling technique. The informants been given a list of semi-structures questions before aninterview session been conducted. The informants been selected from several government agenciesin Negeri Sembilan such as Jabatan Keselamatan dan Kesihatan Pekerjaan Negeri Sembilan,UiTM Seremban Campus, UiTM Rembau Campus, Kementerian Kemajuan Luar Bandar dan Wilayah Negeri Sembilan and Jabatan Pelajaran Negeri Sembilan. From the findings it showsthat reasons for ineffective system of procurement due to lack of standardization and complicatedprocedures. In addition, most of the staff still lack of skills in using the system. Some of the staffalso are not accountable in control the systems especially during bidding process and the maincontributor to ineffectiveness of e- procurement is because of barriers in ICT infrastructures. Theimpacts from e-procurement system that not effective, it will lead to corruption issues that stillincrease due to unfairness towards the qualified suppliers and small-scale contractors. To solvethe problems, it was suggested for the staff to be sent for training and can enhance in term ofmanagement audit to view the performance of the staff in using the system. Despite, themanagement can have instant maintenan